Global Characterization of Metabolic Genes Regulating Survival and Immune Infiltration in Osteosarcoma - Zhu, Zhongpei; Zhang, Min; Wang, Weidong; Zhang, Peng; Wang, Yuqiang; Wang, Limin (Frontiers in Genetics, 2022)
Background: The alterations in metabolic profile of tumors have been identified as one of the prognostic hallmarks of cancers, including osteosarcoma. These alterations are majorly controlled by groups of metabolically active genes. However, the regulation of metabolic gene signatures in tumor microenvironment of osteosarcoma have not been well explained. Objectives: Thus, we investigated the sets of previously published metabolic genes in osteosarcoma patients and normal samples. Methods: We applied computational techniques to identify metabolic genes involved in the immune function of TME, survival and prognosis of the osteosarcoma patients. Potential candidate gene “PAICS” was chosen for further studies in osteosarcoma cell lines for its role in cell proliferation, migration and apoptosis. Results: Our analyses identified a list of metabolic genes differentially expressed in osteosarcoma tissues. Next, we scrutinized the list of genes correlated with survival and immune cells, followed by clustering osteosarcoma patients into three categories; C1, C2 and C3. These analyses led us to choose PAICS as potential candidate gene as it’s expression showed association with poor survival, and negative correlation with the immune cells. Furthermore, we established that loss of PAICS induced apoptosis and inhibited proliferation, migration and wound healing in HOS and MG-63 cell lines. Finally, the results were supported by constructing and validating a prediction model for prognosis of the osteosarcoma patients. Conclusion: Here, we conclude that metabolic genes specifically PAICS play an integral role in the immune cells infiltration in osteosarcoma TME as well as cancer development & metastasis.